Organocatalytic Asymmetric Condensation/Keto–Enol Tautomerization Tandem Reaction: Access to Cyclobutanone α‐Amino Acid Ester Derivatives. Issue 4 (April 2014) - Frongia, Angelo; Melis, Nicola; Serra, Ilaria; Secci, Francesco; Piras, Pier Paolo; Caboni, Pierluigi
Abstract A practical method for the synthesis of optically active α‐amino cyclobutanones has been developed, via an organocatalytic asymmetric condensation reaction between racemic 2‐hydroxycyclobutanone and chiral N‐alkyl‐α‐amino acid ester derivatives.